Restoration of degraded land through Moso bamboo (Phyllostachys pubescens) plantation in the Mid-hills of Nepal - Gautam, G. P.; Aryal, R. R.; Lamichhane, P. (Banko Janakari, 2018)
Not available. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page:150-153